Prediction of the Sensitivity of Avian Species to the Embryotoxic Effects of Dioxin-like Compounds - Mohammad Reza, Farmahin Farahani (Université d'Ottawa / University of Ottawa, 2013)
The main goal of this thesis was to develop new methods and knowledge that will explain and predict species differences in sensitivity to dioxin-like compounds (DLCs) in birds. The important achievements and results obtained from the four experimental chapters of this thesis are summarized as follow: (1) an efficient luciferase reporter gene (LRG) assay was developed for use with 96-well cell culture plates; (2) the results obtained from LRG assay were shown to be highly correlated to available in ovo toxicity data; (3) amino acids at positions 324 and 380 within the aryl hydrocarbon receptor 1 ligand binding domain (AHR1 LBD) were shown to be responsible for reduced Japanese quail (Coturnix japonica) AHR1 activity to induce a dioxin-responsive reporter gene in comparison to chicken (Gallus gallus domesticus), and ring-necked pheasant (Phasianus colchicus) AHR1 in response to different DLCs; (4) AHR1 LBD sequences of 86 avian species were studied and differences at amino acid sites 256, 257, 297, 324, 337 and 380 were identified. It was discovered that only positions 324 and 380 play a role in AHR1 activity to induce a dioxin-responsive gene; (5) in COS-7 cells expressing chicken AHR1, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and 2,3,4,7,8-pentachlorodibenzofuran (PeCDF) are equipotent inducers of the reporter gene and bind with similar affinity to chicken AHR1, however, in the cells expressing pheasant, Japanese quail and common tern (Sterna hirundo) AHR1, PeCDF is a stronger inducer than TCDD. PeCDF also binds with higher affinity to pheasant and quail AHR1 than TCDD. The results of this thesis show that embryo lethal effect of DLCs in avian species can be predicted by use of two new non-lethal methods: (1) the LRG assay and (2) determination of the identity of the amino acids at positions 324 and 380. The findings and methods described in this thesis will be of use for environmental risk assessments of DLCs.